Análisis del sistema de intermediación financiera indirecta del departamento de Loreto y Ucayali periodo 2015-2020 - Saldaña Acosta, Omar Alain (2023)
The objective is to compare the indirect financial intermediation system of the Department of Loreto and Ucayali, period 2015-2020. The type of research is of a descriptive level and a quantitative approach, with a non-experimental research design, of a comparative descriptive longitudinal type. The population is finite, it was made up of 14 financial entities from Loreto and 15 from Ucayali, the technique was the census, of intentional non-probabilistic sampling. The collection technique was documentary analysis, and the instrument was content analysis, with an interval scale. The result of the first dimension, it was proved that there is a significant difference between the behavior of the deficit agents between the Departments of Loreto and Ucayali. The second dimension, it was proved that there is a significant difference between the behavior of surplus agents between the Departments of Loreto and Ucayali, the third dimension, it was proved that there is no significant difference between the delinquency rate of the Departments of Loreto and Ucayali, and the last dimension, it was proven that there is a significant difference between the evolution of the financing deficit of the Department of Loreto and Ucayali, period 2015-2020. We conclude that there is no significant difference between the indirect financial intermediation system of the Department of Loreto and the Department of Ucayali, in the period 2015 to 2020.